2020
DOI: 10.1039/c9ta11237e
|View full text |Cite
|
Sign up to set email alerts
|

A copper-clad lithiophilic current collector for dendrite-free lithium metal anodes

Abstract: A flexible copper-clad lithiophilic current collector was designed for high coulombic efficiency dendrite-free Li metal anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…In addition, the high-resolution zoomed in SEM image of the surface cracks revealed abundant Li dendrites and unhinged “dead” Li (Figure S24b), likely because of the centralized Li + flux in these cracks as a result of the SEI break-down. Thus, the continuous formation of unstable SEI and dead Li on the bare Li electrode could be the major cause of capacity fading. , In contrast, only some small cracks were observed on the surface of Li@NF, showing a generally smooth and flat morphology without evident dendrites (Figure S24c,d). Therefore, as a result of the improved structural integrity and suppressed dendrite formation, Li@NF demonstrated better cycling stability in the full cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high-resolution zoomed in SEM image of the surface cracks revealed abundant Li dendrites and unhinged “dead” Li (Figure S24b), likely because of the centralized Li + flux in these cracks as a result of the SEI break-down. Thus, the continuous formation of unstable SEI and dead Li on the bare Li electrode could be the major cause of capacity fading. , In contrast, only some small cracks were observed on the surface of Li@NF, showing a generally smooth and flat morphology without evident dendrites (Figure S24c,d). Therefore, as a result of the improved structural integrity and suppressed dendrite formation, Li@NF demonstrated better cycling stability in the full cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the continuous formation of unstable SEI and dead Li on the bare Li electrode could be the major cause of capacity fading. 49,50 In contrast, only some small cracks were observed on the surface of Li@NF, showing a generally smooth and flat morphology without evident dendrites (Figure S24c,d). Therefore, as a result of the improved structural integrity and suppressed dendrite formation, Li@NF demonstrated better cycling stability in the full cells.…”
mentioning
confidence: 99%
“…[106,107] Since electroplating, which effectively activates metal deposition, can only be performed on conductive substrates, conductive materials such as metal particles, carbon materials, or conducting polymers should be preferentially introduced through various approaches, including wet (i.e., electroless plating) or dry (i.e., sputtering, e-beam evaporation, or carbonization) processes. [54,108,109] In the electroplating process, because the metal ions are first adsorbed and then electrically reduced on the substrate (i.e., cathode side) with conducting sites, the surface coverage of conducting seeds on the substrate is very important for uniform deposition of the metal layer. An et al reported that electrodeposition of a Cu layer onto electrospun polyacrylonitrile (PAN)-based elastomeric nanofibers could produce a transparent flexible conductor (Figure 2h−j).…”
Section: Electroless Plating/electroplatingmentioning
confidence: 99%
“…Therefore, appropriate surface modification strategies must be explored to significantly enhance the affinity between the Li and 3D skeletons. The decoration of 3D skeletons with lithiophilic substances is one of the most effective ways, and a reasonable design of micro/nanostructured lithiophilic layer on 3D skeletons facilitates the improvement of the wettability of Li metals, resulting in uniform Li deposition [36][37][38][39][40]. The present metalorganic framework (MOF)-derived pathway is an effective strategy to grow controllable hollow/porous structures and easily introduce lithiophilic N-functional groups or precursors for the conversion to lithiophilic metal oxides [41][42][43].…”
Section: Introductionmentioning
confidence: 99%